2017
DOI: 10.3324/haematol.2017.177485
|View full text |Cite
|
Sign up to set email alerts
|

Micro-ribonucleic acid-155 is a direct target of Meis1, but not a driver in acute myeloid leukemia

Abstract: Micro-ribonucleic acid-155 (miR-155) is one of the first described oncogenic miRNAs. Although multiple direct targets of miR-155 have been identified, it is not clear how it contributes to the pathogenesis of acute myeloid leukemia. We found miR-155 to be a direct target of Meis1 in murine Hoxa9/Meis1 induced acute myeloid leukemia. The additional overexpression of miR-155 accelerated the formation of acute myeloid leukemia in Hoxa9 as well as in Hoxa9/Meis1 cells in vivo. However, in the absence or following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Given a previous study indicating MEIS1 upregulation of FLI1 in normal hematopoiesis [ 29 ], we hypothesised that a positive feedback loop may exist between FLI1 and MEIS1 in AML. Since MEIS1 levels are frequently elevated in normal karyotype AML (CN-AML), we used the murine Hoxa9/Meis1 AML model as a surrogate for CN-AML and performed Meis1 ChIP-seq analysis where we overexpressed HA-tagged wildtype Meis1 or an HA-tagged DNA binding mutant Meis1 (deltaHD-Meis1) with Hoxa9 [ 21 , 30 ]. We looked for Meis1 binding sites enriched in Hoxa9/Meis1 that were absent or less enriched for deltaHD-Meis1 binding in Hoxa9/deltaHD-Meis1.…”
Section: Resultsmentioning
confidence: 99%
“…Given a previous study indicating MEIS1 upregulation of FLI1 in normal hematopoiesis [ 29 ], we hypothesised that a positive feedback loop may exist between FLI1 and MEIS1 in AML. Since MEIS1 levels are frequently elevated in normal karyotype AML (CN-AML), we used the murine Hoxa9/Meis1 AML model as a surrogate for CN-AML and performed Meis1 ChIP-seq analysis where we overexpressed HA-tagged wildtype Meis1 or an HA-tagged DNA binding mutant Meis1 (deltaHD-Meis1) with Hoxa9 [ 21 , 30 ]. We looked for Meis1 binding sites enriched in Hoxa9/Meis1 that were absent or less enriched for deltaHD-Meis1 binding in Hoxa9/deltaHD-Meis1.…”
Section: Resultsmentioning
confidence: 99%
“…HOXA9 gene expression pattern has been investigated in AML [22]. Yet, there is still a lack of evidence concerning its association with MEIS1 gene expression [23].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that miR-155 can act as an accelerator to promote the development of acute. [9][10][11] In addition to blood diseases, miR-155 is also closely related to the development of solid tumors. The study found that miR-155 plays a key role in promoting the progression of glioma and can be a prognostic factor for the survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-155 is also closely related to tumors. [9][10][11][12][13][14][15] Especially, it has been found that miR-155 is upregulated in the liver tissues of patients. [16][17][18] So far, the role of miR-155 in the development of human liver cancer has not been clarified.…”
Section: Introductionmentioning
confidence: 99%